Biogeochemical prospecting for gold at the Yellowknife City Gold Project, Northwest Territories, Canada: Part 1 - Species optimization. (October 2022) - Ghorbani, Zohreh; Sexton, Alan; Van Loon, Lisa L.; Banerjee, Neil R.
Abstract: The Yellowknife City Gold Project (YCGP), located close to the city of Yellowknife, Northwest Territories, Canada, is exploring and drilling the extension of the Au-bearing shear zones that host the Giant and Con Mines. A biogeochemical survey was conducted over the Crestaurum and Barney deposits, which are hosted within two well-known high Au grade shear zones at the YCGP. A total of 625 samples were collected from the alder ( Alnus incana ) (n = 76), Labrador tea ( Ledum groenlandicum ) (n = 40), black spruce ( Picea mariana ) (n = 189), and juniper ( Juniperus) (n = 320), and analyzed using ICP-MS. Robust statistical analyses were applied to biogeochemical data to (1) identify the biogeochemical response in plant samples with respect to the underlying mineralogy, (2) detect the most preferred plant species in the study area, and (3) identify Au pathfinder elements and subsequently zones of Au enrichment. Principal component analysis (PCA) and K-means clustering analysis were employed to achieve these objectives. The preliminary statistical analysis showed that plant samples can successfully accumulate anomalous Au values up to 147 ppb. Also, it showed that black spruce and Labrador tea can accumulate higher concentrations of Au than alder and juniper. According to the PCA, mineralization/geological (PC1) and physiological (PC2) factors control the distribution of elements in plant samples. According to K-means clustering, plant samples were classified into three clusters based on the vegetation type and their affinity to accumulate suites of elements. Black spruce samples were identified as the optimum sample media for biogeochemical exploration at the YCGP as they were clustered in proximity to the mineralization/geological factor (PC1) responsible for loading vectors of Au, Ag, As, Se, Bi, Pb, Cu, Co, Fe, Zn, Cd, Tl, and Cr. Au is strongly correlated with its pathfinder elements (Ag, As, Se, Bi, Tl and Sb), specifically in the south of the Crestaurum Shear. The presented results in this study demonstrate that zones of Au enrichment can be detected using biogeochemical and robust statistical methods. Highlights: Plant species optimizations for biogeochemical exploration at the Yellowknife City Gold Project. Application of principal component analysis and clustering analysis to biogeochemical exploration. Biogeochemical prospecting for gold at the Crestauruma and Barney Shears. Plant-substrate relationship using principal component analysis. Geochemical factors controlling the distribution of elements in plant samples.